Gasification : its role in the future technological and economic development of the United Kingdom - Hedley, A. B., (Alan B.); Ferguson, F. (London ; New York : Elsevier Applied Science ; New York, NY, USA : Sole distributor in the USA and Canada, Elsevier Science Pub. Co., 1989)
36